205k views
1 vote
No random answers or links, please.

No random answers or links, please.-example-1
User Babu James
by
5.2k points

2 Answers

3 votes

Answer:

1

Explanation:

By question it's given that ,

=> h(x) = -x - 1

  • For finding h(-2) , substitute x = -2 .

=> h(-2) = -(-2)-1

=> h(-2) = 2 - 1

=> h(-2) = 1

Hence the required answer is 1.

User Alex Blasco
by
5.4k points
6 votes

Answer:

the ans is 1 hope ut may help u

Explanation:

x=-2

x = -(-2) -1

x=2-1

x=+1

User Bryji
by
5.3k points